Risk prediction in patients with low-flow, low-gradient aortic stenosis and reduced ejection fraction undergoing TAVI. Issue 1 (5th January 2022) - Ludwig, Sebastian; Goßling, Alina; Seiffert, Moritz; Westermann, Dirk; Sinning, Jan-Malte; Sugiura, Atsushi; Adam, Matti; Mauri, Victor; Frank, Derk; Seoudy, Hatim; Rudolph, Tanja; Potratz, Max; et al.
Abstract : Objective: Patients with low-flow, low-gradient aortic stenosis (LFLG AS) and reduced left ventricular ejection fraction (LVEF) are known to suffer from poor prognosis after transcatheter aortic valve implantation (TAVI). This study aimed to develop a simple score system for risk prediction in this vulnerable subset of patients. Methods: All patients with LFLG AS with reduced EF and sufficient CT data for aortic valve calcification (AVC) quantification, who underwent TAVI at five German centres, were retrospectively included. The Risk prEdiction in patients with Low Ejection Fraction low gradient aortic stenosis undergoing TAVI (RELiEF TAVI) score was developed based on multivariable Cox regression for all-cause mortality. Results: Among all included patients (n=718), RELiEF TAVI score variables were defined as independent predictors of mortality: male sex (HR 1.34 (1.06, 1.68), p=0.013), underweight (HR 3.10 (1.50, 6.40), p=0.0022), chronic obstructive pulmonary disease (HR 1.55 (1.21, 1.99), p=0.001), pulmonary hypertension (HR 1.51 (1.17, 1.94), p=0.0015), atrial fibrillation (HR 1.28 (1.03, 1.60), p=0.028), stroke volume index (HR 0.96 (0.95, 0.98), p<0.001), non-transfemoral access (HR 1.36 (1.05, 1.76), p=0.021) and low AVC density (HR 1.44 (1.15, 1.79), p=0.0012). A score system was developed ranging from 0 to 12 points (risk of 1-year mortality: 13%–99%). Kaplan-Meier analysis for low (0–1 points), moderate (2–4 points) and high RELiEF TAVI score (>4 points) demonstrated rates of 18.0%, 29.0% and 46.1% (p<0.001) for all-cause mortality and 23.8%, 35.9% and 53.4% (p<0.001) for the combined endpoint of all-cause mortality or heart failure rehospitalisation after 1 year, respectively. Conclusions: The RELiEF TAVI score is based on simple clinical, echocardiographic and CT parameters and might serve as a helpful tool for risk prediction in patients with LFLG AS and reduced LVEF scheduled for TAVI.